العلماء: دورهم الدعوي واقسامهم عند ابو حامد الغزالي - Farid, Achmad (Institut Agama Islam Syarifuddin Lumajang, 2022)
This article aims to explain the concept of the division of scholars according to Imam Al-Ghazali in his phenomenal book Ihya' Ulumiddin, without exception, in theoretical and methodological aspects of preaching to these scholars. In the current era of technological progress, there is a crisis regarding the identity of the clergy. Especially for ordinary people, it becomes difficult in itself to determine scholars who deserve to be role models and role models. Not infrequently, with a good turban and a good one, there are some people who claim to be a cleric, but do not have the slightest capacity as a cleric, both intellectually and morally. Fame and followers have been obtained but not balanced with adequate knowledge will eventually lead the people to the brink of astray. By using the research literature method, especially from the books of Imam Al-Ghazali, it is hoped that this paper can answer the concerns above and be able to identify the Islamic scholars and self-reflection from bad and world-oriented scholars.